Eksplorasi Nilai Budaya Jawa dalam Kumpulan Cerita Kisah Tanah Jawa ‘Jagat Lelembut’ Karya Mada Zidan (Mbah Kj) dan Bonaventura D. Genta - Fita, Salsa Delia; Pamungkas, Onok Yayang (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
This research examines the exploration of Javanese cultural values in the story collection Tales of the Land of Java 'Jagat Lesoft' by Mada Zidan (Mbah KJ) and Bonaventura D. Genta. The approach used is a literary anthropology approach and a mythopoic approach. The method used in this research uses hermeneutics. The data taken in this research is in the form of text quotations which contain Javanese cultural values and the data source which is the subject of this research was obtained by researchers from the collection of Javanese Land Stories 'Jagat Lesoft' by Mada Zidan (Mbah KJ) and Bonaventura D. Genta. The data collection technique used is using library techniques, listening and taking notes. The data validity technique used in this research uses triangulation techniques. Data analysis techniques in this research include data collection, data reduction, data presentation, and drawing conclusions. Based on the results of research that has been carried out, Javanese cultural values such as belief values: taboos, belief values: worship rituals, spiritual values, belief values: in God, belief values: in supernatural knowledge, belief values: in supernatural figures, obedience values , tolerance values, religious values, moral values and commendable morals. The Javanese cultural values that dominate in this research are cultural values related to trust. It seems that this story has a strong spirit about the beliefs of Javanese society. This form of belief has an important role as a form of maintaining local wisdom which is the identity of Javanese society. Thus, the important message in this research is that it can contribute to strengthening the identity of Javanese society.Keywords: values, Javanese culture, anthropology, mythology, story of the land of Java